Application of arc-shaped electrostatic sensors for monitoring the flow behaviour at top and bottom section of a pneumatic conveying pipeline. (15th November 2020) - Kumar, Amit; Deng, Tong; Bradley, Michael S.A.
Abstract: Measurement of particle's charge in the pneumatic conveying systems can be used to monitor the flow behaviour (stable or unstable) in dilute phase pneumatic conveying. The particle's charge can be measured by inductive electrostatic sensors and converted into a time-domain signal, which is called an electrostatic signal. However, with popular ring-shaped sensors, limited information can be obtained on electrostatic signals. Arc-shaped electrostatic sensors have some advantages on measuring particle's charge at different locations such as the top or bottom of the pipe. To get enough information about the flow behaviour, the electrostatic signal needs to be processed by using different data analysis techniques. In this study, electrostatic signals are recorded at the top and bottom section of the pipe at varied conveying air velocity and at a constant solid feed rate. These different air velocities result in a stable dilute flow and unstable dune flow in the pipeline. The electrostatic signals of stable and unstable flows are analysed by using Fast Fourier Transform (FFT) and Hilbert-Huang Transform (HHT) techniques for real-time monitoring of flow behaviour in a pilot pneumatic conveyor. The results show that HHT analysis is far better than FFT for distinguishing between stable dilute and unstable dune flow. Where FFT only capture the difference in the flow behaviour with only top electrostatic sensor's signal but HHT work with both top and bottom sensor's signals. HHT does not only distinguish between stable and unstable flows but also shows the consistency in the results of the 80 ​s, 10 ​s and 5 ​s of the data analysis, which is the main requirement for any technique to be used for real-time monitoring systems. This clearly represents a huge benefit for control and monitoring in the pneumatic conveying systems.